2019
DOI: 10.3390/w12010036
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations in Seston C:N:P Stoichiometry in a Large Eutrophic Floodplain Lake (Lake Taihu): Do the Sources of Seston Explain Stoichiometric Flexibility?

Abstract: Although sources of seston are much more complicated in lakes compared to oceans, the influences of different sources on the spatiotemporal variations in seston stoichiometry are still underexplored, especially in large eutrophic floodplain lakes. Here, we investigated seston stoichiometric ratios across a typical large eutrophic floodplain lake (Lake Taihu, East China) over one year. In addition, we used the n-alkane proxies to examine the influence of the seston source on seston stoichiometry variation. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These results suggested that the concentration of approximately 8 mg l -1 was the maximum threshold of M. densa for N demand. This concentration was significantly higher than the N concentration in most lakes and reservoirs [35,36], which suggested that M. densa could grow rapidly in most waters and N concentrations in natural waters would not restrict the growth of M. densa.…”
Section: P (Mg L -1 )mentioning
confidence: 87%
“…These results suggested that the concentration of approximately 8 mg l -1 was the maximum threshold of M. densa for N demand. This concentration was significantly higher than the N concentration in most lakes and reservoirs [35,36], which suggested that M. densa could grow rapidly in most waters and N concentrations in natural waters would not restrict the growth of M. densa.…”
Section: P (Mg L -1 )mentioning
confidence: 87%
“…The decreased denitrification during algal blooms may be just the redistribution of the N removal amount over the whole year. Secondly, in the growing season (from late spring to early autumn), the POM derived from algal sources was dominant in all areas of northern Lake Taihu, and in the senescence season (from late autumn to early spring), the spatial differences of POM sources between the littoral area and the centre area of the lake are significant due to the influence of terrestrial inputs or macrophytes (Cai et al., 2020). Nitrate ammonifiers at the centre area of the lake may be adapted to use algal detritus but nitrate ammonifiers in littoral area may not be, which is likely to lead to the different response of DNRA on POM sources (Salk et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem feedback between biological factors (such as consumer stoichiometry) and environmental factors (such as resource stoichiometry) in biological systems is under homeostatic regulation, and has effects through a reciprocal influence of the supply and demand balance of elements between organisms, and between the organism and the environment. From studies on marine life, for example plankton (phytoplankton and zooplankton) [44][45][46], aquatic hyphomycetes [47,48], algae [49,50] and daphnia [51], our understanding of consumer stoichiometry, consumer population stability and community organization structure has greatly increased. However, large variations have been observed in the nutrient content of autotrophic organisms in different life periods, leading to large variations in stoichiometric ratios (such as C:N:P).…”
Section: Keyword Cluster Analysismentioning
confidence: 99%